(untitled) - Thomsen, Erik (New York, 2002)
OLAP enables users to access information from multidimensional data warehouses almost instantly, to view information in any way they like, and to cleanly specify and carry out sophisticated calculations. Although many commercial OLAP tools and products are now available, OLAP is still a difficult and complex technology to master.
Keywords: Decision support systems,Hệ thống hỗ trợ quyết định